EFFECT OF 6 WEEKS OF AQUATIC TRAINING ON THE PAIN STATE OF ACTIVE MILITARY POLICE OFFICERS IN THE METROPOLITAN CITY OF JOÃO PESSOA – PB - Lordão, Filipe Elton Fernandes; Di Pace França, Clizaldo Luiz Maroja; Dantas, Pedro Augusto Mariz; Di Pace França, Arthur Maroja; Arcoverde, Abdallah Salomão; Montenegro, Rafael Petrucci Negócio; Ramalho, Wesley Crispim; Lucena, Caroline de Lima Alexandre; Montenegro, Ramon Cunha; de Lucena, Pedro Henrique Marques; Gomes, Silvana Nóbrega (Seven Editora, 2025)
The need for effective physical fitness in the daily lives of military police officers plays an important role not only in their professional performance but also in their individual quality of life. Objective: To assess the effect of 6 weeks of aquatic training on the pain status of active-duty military police officers in the metropolitan region of João Pessoa, Paraíba. Methodology: This is a descriptive, quasi-experimental, and quantitative study. The sample consisted of 35 military police officers of both sexes, with a mean age of 41.67 years and a standard deviation of ± 8.729. The data collection instrument was a questionnaire to assess musculoskeletal pain in exercisers. Data collection occurred before and after 6 weeks of intervention. The intervention consisted of aquatic training using a combination of continuous and interval training methods, performed three days a week, with each class lasting 60 minutes, at moderate to vigorous intensity, and monitored by the subjective perception of exertion scale. For data analysis, Excel was used to tabulate the data, and descriptive analysis was performed using SPSS version 21. Results: 50% of participants experienced pain in some area of the body pre- and post-intervention at rest, but there was a 20% reduction during exercise. The areas most affected by pain during exercise were the knees, lower back, and shoulder, with post-intervention reductions of 25%, 20%, and 10%, respectively. There were also reductions in all functional aspects and psychosocial factors, with a notable reduction in pain during exercise. Conclusion: Six weeks of aquatic training reduced musculoskeletal pain in military police officers, improving their quality of life and contributing to their professional performance. DOI: https://doi.org/10.56238/sevened2025.029-010